Pemikiran Pendidikan Islam Pada Masa Awal - Novita Sari; Desi Ratna Sari; Dwi Noviani; Paizaluddin Paizaluddin (IHSANIKA : Jurnal Pendidikan Agama Islam, 2023)
Islamic education is education that is based on the teachings of Islam itself. The Qur'an and Sunnah are the main guidelines in implementing its operations. In the current era, Islamic education continues to strive to improve its quality, so that every effort is made. One of these efforts is, for example, reviewing with a sharp analysis how Islamic education that the Prophet Muhammad SAW implemented at the beginning Islamic history itself. It is hoped that this study of the early history of Islam can refresh our memories about the figure of the Prophet Muhammad SAW. so that it can be successful in developing human beings who have previously experienced crises in various aspects of life. Based on the studies that have been discussed, it turns out that the Prophet Muhammad was able to raise their dignity and even become a factory of knowledge and culture for approximately six centuries.